Protocol engineering issues for open systems communications. - Aleem, Syed A. (University of Ottawa (Canada), 1990)
In this thesis we present real design criteria and design building blocks in a highly procedural way starting from the specification to the implementation stage. A subset of a real protocol, namely ISDN Q.931 (CCIT3), written in informal English will be translated to a formal specification using Estelle as the formal description technique. A means of incorporating the design criteria into the formal description of the protocol is presented and illustrated with Q.931 as example. This thesis will also derive the services a protocol expects from the operating system. Those services will be summarized and standardized in order to limit variability in the design process of a protocol. The system interface which has been a major source of variation in protocol implementation, will reduce to a set of a few well defined standard system calls by assuming a proposed standard operating system interface. This interface standard appears to be sufficient to allow the automatic development of complete protocol software. (Abstract shortened by UMI.)
Keywords: Computer Science.